KREATIVITAS SURYATI DALAM MENYAJIKAN CENGKOK SINDHENAN BANYUMASAN - Muriah Budiarti; Siswati Siswati (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2019)
This research topic is raising about Suryati as one of the Banyumas sinden who contributed to the development of Banyumas style of music. Suryati’s artistic process is formed by several factors, Suryati’s family environment support helped his success in finding the soul of sindhen in himself. that are The Suryati’s selfishness and her persistence which are very important factors that shaped her creativity. So that her styles and “anggit” that Suryati brought were the essence of her artistic environment. Suryati’s character is identical with prenes, meticulous, actualized titen into suryati Sindhenan style twists. So people who hear Suryati’s twisted can guess that it is a form of Suryati’s twisted characteristic. With the ethnographic method, several factors forming the creativity of Suryati’s artistic style will be explained. One of the results of Suryati’s efforts was to introduce “gendhing Banyumasan” in Java and its surrounding area.Keywords: Sinden, karawitan, Banyumasan, Suryati, ethnography.